Effective actions to support transition: exploring the experience of public schools in Chile - Jadue-Roa, Daniela S.; Gómez, David M.; Soto-Sarmiento, Mayer; Amigo-López, Thierry; Grace, Rebekah (Frontiers in Education, 2025)
This study aimed to explore the nature of the technical-pedagogical support provided by Public Education Local Services in Chile for implementing Decree 373, as perceived by school leaders and teachers. It examined how this collaboration facilitated the design and implementation of effective actions to support the successful progression of children from kindergarten to first grade. Previous work in the field of transition suggests that effective transition programmes consider the perspectives of all actors—children, families, and practitioners—and are more likely to succeed when there are positive leaders within both the management and pedagogical teams. This study focused on the perspectives of practitioners and management teams within five different public schools, employing a multiple case study design and a mixed-methods approach with a predominantly qualitative focus. Data was collected through a questionnaire comprising both closed-ended and open-ended questions. Findings show that the implementation of this Decree is still in its initial stages and faces challenges due to the new structure within the public education system. Furthermore, in terms of leadership, the study highlights the need to adopt more horizontal and democratic forms of leadership both within the system and in individual schools. Educators and teachers report being motivated to work collaboratively and wanting to be included in future initiatives. The experiences of these school staff members provide meaningful insights into how to advance the implementation of the public education system in partnership with schools.